Associations between shift schedule characteristics with sleep, need for recovery, health and performance measures for regular (semi-)continuous 3-shift systems. (September 2016) - van de Ven, Hardy A.; Brouwer, Sandra; Koolhaas, Wendy; Goudswaard, Anneke; de Looze, Michiel P.; Kecklund, Göran; Almansa, Josue; Bültmann, Ute; van der Klink, Jac J.L.
Abstract: In this cross-sectional study associations were examined between eight shift schedule characteristics with shift-specific sleep complaints and need for recovery and generic health and performance measures. It was hypothesized that shift schedule characteristics meeting ergonomic recommendations are associated with better sleep, need for recovery, health and performance. Questionnaire data were collected from 491 shift workers of 18 companies with 9 regular (semi)-continuous shift schedules. The shift schedule characteristics were analyzed separately and combined using multilevel linear regression models. The hypothesis was largely not confirmed. Relatively few associations were found, of which the majority was in the direction as expected. In particular early starts of morning shifts and many consecutive shifts seem to be avoided. The healthy worker effect, limited variation between included schedules and the cross-sectional design might explain the paucity of significant results. Highlights: Researchers/consultants use ergonomic criteria in designing or advising on rosters. Nine shift schedules were described in terms of eight ergonomic criteria. Sleep, need for recovery, fatigue, health and work functioning were used as outcomes. Associations for ergonomic criteria with outcomes were weak and mostly non-significant. Longitudinal studies including work-related factors are needed.